Identification of non-host resistance genes in wheat to barley yellow rust - Rodrigues, Paula (2004)
Yellow rust, caused by Puccinia striiformis West., is an important foliar disease of wheat and barley throughout the world, and the development of resistant cultivars is the most economical and environmentally friendly method of control. Breeding for resistance to yellow rust has, for decades, been based on the use of race-specific resistance genes, which have shown to be short-lived. Non-host resistance has been studied as a possible source of durable resistance. Two major genes, as well as an undetermined number of minor genes, for non-host resistance to the barley attacking form of yellow rust, P. striiformis f. sp. hordei, have been previously detected in the wheat cultivar ‘Lemhi’. The present study aimed at quantifying and mapping those genes using QTL (quantitative trait loci) mapping procedures. For that purpose, an F2 population of 114 individuals resulting from the cross of resistant ‘Lemhi’ with ‘Chinese 166’, a wheat cultivar susceptible to barley yellow rust, was used as the mapping population. QTL effects and significance were estimated by means of interval mapping and MQM mapping procedures. A map for the F2 population was constructed which included 116 DNA markers (14 SSRs and 102 AFLPs). Two major QTLs have been mapped to chromosome arms 1DS (Psh1) and 2BL (Psh2), with significant LOD values. These two QTLs account for 76.7% of the phenotypic variance for resistance to barley yellow rust. Two other QTLs, with a minor effect, were mapped to chromosome arms 5AL (Psh3) and 6AL (Psh4), explaining 5.1% and 10.9% of the phenotypic variation, respectively. The QTL on 5A was derived from the susceptible variety, ‘Chinese 166’. In all cases the resistance towards P. striiformis f.sp. hordei was associated with a visual chlorosis/necrosis response typical of race-specific, host resistance.